Urban Informality and Its Economic Consequences: An Empirical Study of Slum Effects on Property Values in Asaba Community, Delta State - Benedicta Njideka Okafor (Siber Nusantara Research, 2025)
Urban degradation is caused principally by urbanization process, however, most of the environmental problems in Asaba metropolis suburbs result largely from its unplanned land uses, swampy nature of built areas and weak development control. Other critical problems that bother minds also include lack of open space, poor management of flood channels and substandard housing. This paper discuses the possible intervention strategies in the regeneration effort of Asaba slum area. The research method which is both narrative and statistically descriptive in nature enables the author engage in a detailed literature study of the chronological development of Asaba metropolis with view to determining how the city came about the current level of degenerating infrastructural facilities. The study found that the principle of cooperative leadership by government at all levels is fundamental to making important difference in qualitative development controls of the study area. It however concluded that the duo role of the public and traditional power structure of the community leaders must be involved in the conception and implementation of Delta State environmental planning programmes